Discovery Learning Model on Mathematics Learning at Islamic Private Junior High School Darussalam - Okviani Syafti (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
The study aims to determine whether the mathematics learning outcomes of students who learn discovery learning are better than students who learn conventionally. It also aims to find out whether the mathematics learning outcomes of students with high initial abilities and low initial abilities with discovery learning are better than students who learn conventionally. This type of research is a Quasi Experiment with quantitative approach design and used was a randomized control group only design with treatment by blocks. The population in this study were students of class VII Â Islamic private junior high school or MTsS Darussalam Ampiang Parak, Sutera Sub District, Pesisir Selatan. The research sample was randomly selected,namely students of class VII.1 as the experimental class and VII.2 as the control class. The research data were obtained from the results of the initial ability test and the final test given after the experiment was carried out. Data analysis using t test.The results of the analysis show that: 1) The mathematics learning outcomes of students with discovery learning model are better than those taught by conventional learning, 2) Mathematics learning outcomes of students with high initial abilities and students with low initial abilities with discovery learning learning models of learning arebetter than students with high initial abilities. taught by conventionallearning. The results could be a solution for teachers to provide learning to develop students' ability invention, especially in the discovery of mathematical concepts and problem solving both in learning and in daily life